Neutral evolution in paroxysmal nocturnal hemoglobinuria - Dingli, David (National Academy of Sciences, 2008)
Paroxysmal nocturnal hemoglobinuria is an acquired hematopoietic stem cell (HSC) disorder characterized by the partial or complete deficiency of glycosyl-phosphatidylinositol (GPI)-linked membrane proteins, which leads to intravascular hemolysis. A loss of function mutation in the PIG-A gene, required for GPI biosynthesis, explains how the deficiency of many membrane proteins can result from a single genetic event. However, to date the mechanism of expansion of the GPI(−) clone has not been fully understood. Two hypotheses have been proposed: A selective advantage of GPI(−) cells because of a second mutation or a conditional growth advantage of GPI(−) cells in the presence of an immune attack on normal (GPI(+)) HSCs. Here, we explore a third possibility, whereby the PNH clone does not have a selective advantage. Simulations in a large virtual population accurately reproduce the known incidence of the disease; and the fit is optimized when the number of stem cells is decreased, reflecting a component of bone marrow failure in PNH. The model also accounts for the occurrence of spontaneous cure in PNH, consequent on clonal extinction. Thus, a clonal advantage may not be always necessary to explain clonal expansion in PNH.